Development and Validation of an Interactive E-Book in Physics 9 - Dominado, Noel; Bulaun, Criselle May P.; Quiambao, Cynthia G. (Future Science / FSH-PH Publications, 2023)
The study developed and validated an interactive e-book in Physics in Grade 9 Science to help augment the learning gaps and the least mastered competencies based on the regional diagnostic assessment. The content of the lessons in the interactive e-book was based on the six (6) least learned, most essential learning competencies that were provided by the Department of Education. The material was conceptualized based on objectives, content or parts, and evaluation tools. The developed interactive e-book was validated in terms of content quality, instructional quality, technical quality, and other findings. Based on the results of the validation of the six (6) faculty experts, it revealed that the crafted material was very satisfactory in all the criteria, which means that it was valid and ready for use by the students. The learners evaluated the developed material in terms of content, adequacy of scope, and appropriateness of exercises. It inferred that the interactive e-book was acceptable and reliable for its intended users. The result of this study has a significant implication to teaching Physics to Grade 9 students. It means that the material can serve as supplementary material since the students were engaged in learning and had shown interest when the lesson involved educational technology, and since there are insufficient modern instructional materials in Physics.